HOTS-ORIENTED INDONESIAN LANGUAGE LEARNING IN SENIOR HIGH SCHOOL IN JAMBI - Rustam Rustam; Rasdawita Rasdawita; Priyanto Priyanto (Universitas Negeri Makassar, 2020)
The purpose of this research was to describe the competence of the high school teachers in Jambi in designing, implementing, and evaluating HOTS-oriented Indonesian Language learning. To answer this question, the concept of Indonesian Language learning was employed. This study used a qualitative design with case study technique. The data were comprised of the responses, learning process, and action conducted by the teachers. The respondents were selected using purposive sampling method by considering teacher’s academic qualifications. Data collection was performed through interview accompanied by focused group discussion (FGD), observation and document-ation. The results of this study showed that the Indonesian Language teachers had designed, implemented and evaluated students’ performance in HOTS-oriented Indonesian Language learning. Unfortunately, the teachers were less capable of synergizing the HOTS-oriented learning with pedagogical approaches, such as genre-based (text learning), scientificlearning and CLIL.